Konsolidasi Kinerja Karyawan Ditinjau Dari Motivasi Kerja Dan Disiplin Kerja Di Kantor Camat Kota Padang - Fenia, Selvi Zola (Jurnal Ekonomika Dan Bisnis (JEBS), 2022)
Research with the title "Consolidation of Employee Performance in terms of Work Motivation and Work Discipline at the Padang City Sub-District Office". The object of this research is employees who work in Padang City District. The type of research used in this study is quantitative causality research, the data collection method is by distributing questionnaires. The analysis technique used is multiple linear regression analysis with the help of the SPSS program. The sampling technique in this study uses a saturated sample by analyzing 60 respondents. Based on the results of the analysis, it can be concluded that work motivation has no significant effect on employee performance. work has a positive and significant effect on employee performance.